The Role of Work Motivation in the Relationship between Work Engagement and Job Satisfaction in Retail Workforce - Aesa; Olievia Prabandini Mulyana (Al-Qalam Institue, 2026)
This study aims to examine the effect of work engagement on job satisfaction with work motivation as a mediating variable among retail employees. A quantitative approach with a correlational survey design was employed. Data were collected through self-report questionnaires using the Utrecht Work Engagement Scale (UWES-9), Job Satisfaction Survey (JSS), and Motivational at Work Scale (MAWS). The sample consisted of 81 retail employees selected through purposive sampling. Data analysis was conducted using regression analysis to test the direct relationships among variables. The results indicate that work engagement has a significant negative effect on job satisfaction. In addition, work motivation also shows a significant negative relationship with job satisfaction. These findings suggest that high levels of engagement and motivation do not necessarily lead to higher job satisfaction, particularly in work environments characterized by high operational demands and limited organizational support. From an educational management perspective, the results highlight the importance of managing human resources not only by encouraging engagement and motivation, but also by improving the quality of work experiences, organizational learning, and employee development systems. This study contributes to the literature on work psychology and educational management by emphasizing the contextual nature of employee well-being and providing practical implications for human resource management and workplace learning in service-oriented organizations.